2019
DOI: 10.1063/1.5120554
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of dislocation generation and annihilation in α -Ga2O3 epilayers on sapphire

Abstract: Epitaxial film quality is critical to the success of high-performance a-Ga 2 O 3 vertical power devices. In this work, the origins of threading dislocation generation and annihilation in thick a-Ga 2 O 3 films heteroepitaxially grown on sapphire by the mist-CVD technique have been examined by means of high-resolution X-ray diffraction and transmission electron microscopies. By increasing the nominal thickness, screw dislocations exhibit an independent characteristic with a low density of about 1.8 Â 10 6 cm À2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…As the thickness of the layers increased, the FWHMs of the (10 4) plane reflections rapidly decreased and was saturated to ≈1000 arcsec at a certain thickness (e.g., ≈1.5 µm). The large discrepancy in the FWHM values of the and planes are commonly attributed to the edge and screw dislocations density, respectively, wherein the edge dislocation density is relatively higher than the screw dislocation density [ 27 ]. This indicates that the improved crystallinity of the epitaxial layers could be attributed to the reduction in the edge dislocation density with an increase in the thickness until saturation.…”
Section: Resultsmentioning
confidence: 99%
“…As the thickness of the layers increased, the FWHMs of the (10 4) plane reflections rapidly decreased and was saturated to ≈1000 arcsec at a certain thickness (e.g., ≈1.5 µm). The large discrepancy in the FWHM values of the and planes are commonly attributed to the edge and screw dislocations density, respectively, wherein the edge dislocation density is relatively higher than the screw dislocation density [ 27 ]. This indicates that the improved crystallinity of the epitaxial layers could be attributed to the reduction in the edge dislocation density with an increase in the thickness until saturation.…”
Section: Resultsmentioning
confidence: 99%
“…There are some methods to grow Ga 2 O 3 films, for example, molecular beam epitaxy (MBE), [15] metalorganic chemical vapor deposition (MOCVD), [16] halide vapor phase epitaxy (HVPE) [17] and aqueous-solution spin-coating [18] method. These techniques are generally time-consuming and expensive and the growth rate is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low crystal quality of α-Ga 2 O 3 thin films grown on sapphire substrates is a critical drawback to its potential application. 7,8 In fact, Kaneko et As an alternative way to obtain high-quality and strainrelaxed α-Ga 2 O 3 thin films, the use of a sapphire nanomembrane, a thin substrate of less than 100 nm with air cavities, can be considered. This thin substrate can reduce substrate clamping, which reduces the deterioration of thin film crystallinity caused by lattice and thermal expansion mismatch.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the low crystal quality of α-Ga 2 O 3 thin films grown on sapphire substrates is a critical drawback to its potential application. , In fact, Kaneko et al . reported that an α-Ga 2 O 3 thin film on sapphire has a 10 10 cm –2 threading dislocation density (TDD) caused by a lattice mismatch of 4.81%.…”
Section: Introductionmentioning
confidence: 99%